2019
DOI: 10.21307/ane-2019-011
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins as potential supportive medication for the treatment of epilepsy

Abstract: Epilepsy, one of the most common neurological disorders, is a chronic disease of the brain manifested by seizures due to sudden, spontaneous bioelectrical discharges in nerve cells. An estimated 50 million people worldwide suffer from epilepsy.Antiepileptic drugs are the mainstream treatment for epilepsy; however, the drug resistance occurring in 20-30% of patients and side effects of available medications have resulted in a search for natural remedies that can support disease therapy. Coumarins may be a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…In addition to intensively designed and synthesized chemical compounds with potential antiepileptic properties, a lot of attention is also paid to substances of natural origin, which are increasingly used in research with AEDs in various models of experimental epilepsy [ 10 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to intensively designed and synthesized chemical compounds with potential antiepileptic properties, a lot of attention is also paid to substances of natural origin, which are increasingly used in research with AEDs in various models of experimental epilepsy [ 10 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the above phytochemical constituents are responsible for the anti-epileptic action of the medicine. (8). It is also evidenced that Coumarin has a promising anticonvulsant activity.…”
Section: Introductionmentioning
confidence: 94%
“…It is also found in the drug warfarin which is used as an anticoagulant. Some studies have demonstrated coumarin derivatives for their possibility as a supportive treatment for epileptic seizures [ 51 ]. A good result of acridone-based 1,2,4-oxadiazole derivatives by Khanaposhtani et al in the year 2016 synthesized another series of coumarin-1,2,4-oxadiazole hybrids in the year 2019 [ 6 ].…”
Section: Synthetic Pathway Of Non-nitrogen Heterocyclic Compounds As ...mentioning
confidence: 99%